1993
DOI: 10.1111/j.1476-5381.1993.tb13637.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of ranolazine in guinea‐pig hearts during low‐flow ischaemia and their association with increases in active pyruvate dehydrogenase

Abstract: 1In isolated Langendorff-perfused, electrically-paced, hearts of guinea-pigs, global low-flow-ischaemia (LFI; at 0.7 ml min-') resulted in marked increases in the rates of release of lactate, lactate dehydrogenase (LDH) and creatine kinase (CK) over a 30 min period. At the end of the LFI period, tissue ATP content was significantly reduced from a control value of 11.8 ± 0.8 (5) to 5.6 ± 0.8 (5) JAmol g-' dry weight.2 The presence of ranolazine [(±)-N-(2,6-dimethyl-phenyl)-4[2-hydroxy-3-(2-methoxy-phenoxyl)-pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 17 publications
2
48
0
Order By: Relevance
“…This dose of ranolazine was based on therapeutic levels for angina treatment in humans and may not have provided maximal efficacy in our model. Based on results of other studies describing the cardioprotective effects of ranolazine in isolated perfused hearts (Clarke et al, 1993;Gralinski et al, 1994), concentrations of 15 and 20 M ranolazine were found to be more efficacious than 5 and 10 M, concentrations similar to that achieved in our study. In the present study, the dose used yielded plasma concentrations within the range of clinical therapeutic plasma levels, as was our intention.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…This dose of ranolazine was based on therapeutic levels for angina treatment in humans and may not have provided maximal efficacy in our model. Based on results of other studies describing the cardioprotective effects of ranolazine in isolated perfused hearts (Clarke et al, 1993;Gralinski et al, 1994), concentrations of 15 and 20 M ranolazine were found to be more efficacious than 5 and 10 M, concentrations similar to that achieved in our study. In the present study, the dose used yielded plasma concentrations within the range of clinical therapeutic plasma levels, as was our intention.…”
Section: Discussionmentioning
confidence: 84%
“…Gralinski et al (1994) noted that the increase in tissue calcium seen in control hearts was completely prevented by 20 M ranolazine. In a guinea pig heart model of low-flow ischemia, Clarke et al (1993) found that hearts perfused with ranolazine had less LDH and CK release during the ischemic period and that tissue ATP was preserved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1) is a novel antiischemia and antianginal agent that has been found to be effective to treat chronic angina [1][2][3]. It works by inhibiting fatty acid betaoxidation and by increasing the active fraction of pyruvate dehydrogenase [4,5]. Ranolazine appears to switch adenosine triphosphate (ATP) production away from fatty acid oxidation to more oxygen-efficient carbohydrate oxidation as a substrate for ATP production, especially when free fatty acids are elevated during ischemia [6].…”
Section: Introductionmentioning
confidence: 99%
“…1) is a piperazine derivative developed by Syntex Laboratories, which has been shown to have anti-ischemic action. [2][3][4][5] It's a partial fatty acid oxidation (pFOX) inhibitor. Its mechanism has not been fully understood.…”
mentioning
confidence: 99%